Identification of genes and pathways regulated by the PRH/HHEX transcription factor in endothelial and lymphatic cells - Dahhan, Rania (2024)
The Proline-Rich Homeodomain protein (PRH/HHEX) is recognized as an essential transcription factor in development and in the adult. PRH regulates transcription by binding directly to DNA at specific regions of target genes, often containing specific DNA sequence motifs to which it has a high affinity. Moreover, PRH is also known to interact with many other transcription factors, including activator protein 1 (AP-1) to modulate complex gene regulatory networks either directly or via indirect mechanisms. As a transcriptional regulator, PRH can act either as a transcriptional repressor or as an activator, depending on the context and its interactions with other cofactors. This study aims to better understand the role of PRH in normal vascular homeostasis through the manipulation of PRH expression in Human Umbilical Vein Endothelial Cells (HUVECs) and Human Dermal Lymphatic Endothelial Cells (HDLECs). Endothelial cells line blood and lymphatic vessels, orchestrating processes including tube formation, cell extravasation, and vessel permeability which are essential for maintaining the integrity and functionality of the vascular system. This thesis demonstrates that PRH regulates angiogenic tube formation as well as the proliferation, and migratory behaviour of blood and lymphatic endothelial cells. Adenoviral overexpression of PRH results in decreased proliferation, decreased migration in wound closure assays, and decreased angiogenic tube formation in HUVECs and HDLECs. Conversely, RNA interference (RNAi) knockdown of PRH in HUVECs and HDLECs results in increased cell proliferation, increased migration in wound closure assays, and increased angiogenic tube formation. Interestingly, PRH protein expression varies in correlation with endothelial cell density, where confluent HUVECs exhibit higher PRH levels than sub-confluent HUVECs indicating a role for PRH in modulating cellular behaviour during proliferation and quiescence. Further exploration through whole transcriptome analysis using RNA sequencing analysis post-PRH manipulation indicates that blood and vascular related genes are over-represented in the Differentially Expressed Genes (DEGs); genes that show a significant change in expression levels between normal and altered PRH conditions. This identified wound healing, cell adhesion, cell motility, and circulatory system development as significantly enriched biological processes regulated by PRH.